THE ACTIVITIES OF THE KASHKADARYA WRITERS' UNION: PROMOTING LITERATURE AND CULTURE - Akhmatov A. A.; Ergasheva B. P. (Web of Journals Publishing, 2025)
The Qashqadaryo Writers' Union plays a significant role in the literary and cultural life of the Qashqadaryo region in southern Uzbekistan. This article discusses the activities of the union during the Soviet period and in the post-independence era, focusing on its contributions to the development of literature, the promotion of regional writers, and the nurturing of new literary talent. The article explores the impact of Soviet ideological control on literature, the shift towards national and regional literature after Uzbekistan's independence in 1991, and the union's efforts to support young writers through competitions and workshops. Additionally, the article examines the role of the union in organizing literary events, advocating for writers' rights, and fostering international literary collaborations.
Keywords: Qashqadaryo Writers' Union, Soviet period, post-independence era, Literature, Writer support, Literary festivals, Young writers, National literature, Regional literature, Literary research, Literary competitions, Literary rights, Uzbek literature.